Implementasi Hukum Waris Islam di Jl. Sabilal Muhtadin Lr. Sabilal IX Tembilahan Hulu 2023 - Madenia, Muhammad Ilham; Herdiansyah; Istiqomah, Nurul; Gunawan, Rina; Sahrina; Mohd. Avandi (Jurnal Indragiri Penelitian Multidisiplin, 2024)
Distribution of inheritance is one of the important things in Islamic law. In addition, scholars often discuss and study this issue from the classical period to the present. So it can be seen that the division of inheritance is a complex thing to study. This study aims to analyze the systematics or procedures for the process of distributing inheritance in the Sabilal IX community. The analytical method used in this study is the interview method to find empirical information or field facts about people's understanding of the distribution of inheritance. There are various forms of distribution of inheritance, especially in the Sabilal IX community that we encountered, such as, distribution of inheritance according to Islamic law, equal distribution and there are some communities that distribute inheritance before the testator dies, and there are those who do not distribute inheritance at all. Therefore, there is a need for a deeper understanding to study the procedures for distributing inheritance assets according to Islamic law in the community, especially in the scope of Sabilal IX where the majority are Muslim communities. As a Muslim, using Islamic inheritance law in dividing inheritance is an obligatory thing to do. Because the provisions for heirs have been stipulated in the Qur'an, making it easier to distribute inheritance in society.